TASAWUF HAMKA SEBAGAI SOLUSI KONTEMPORER UNTUK GEN. Z DITENGAH TANTANGAN BUDAYA POP COGIL DAN CEGIL - Fernanda, Ahmad (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This research aims to establish modern Sufism, advocated by Buya Hamka, as a solution for navigating toxic lifestyles that foster a culture of arrogance and superficiality. The research method utilized in this article is qualitative, employing a descriptive analysis approach to explore Buya Hamka's thoughts on modern Sufism as a reference for the restless Gen Z generation, troubled by their own existential concerns. Data collection involves the use of questionnaires administered through Google Forms and library research. The primary data sources include processed responses from respondents gathered through Google Forms, while secondary data sources comprise Buya Hamka's book